1996
DOI: 10.1007/bf01797082
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic differences in mortality. A life course approach

Abstract: "Differential mortality in Norway has been studied on the basis of a sample of data derived from the linkage of the 1960, 1970, and 1980 censuses to vital registration records. Based on the hypothesis that the determinants of survival act in interaction, two models are proposed. The first is based on states defined at each observation period by the conjunction of attributes characterizing each individual. The second model considers the chronological order of the states. Logistic regression applied to the lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 9 publications
0
28
0
1
Order By: Relevance
“…The "healthy worker survivor effect" is an ongoing process where those who stay in a specific occupation tend to be healthier than those who exit employment (41). The attrition analysis showed that respondents who were included in the trajectory analysis were slightly younger, more often upper white-collar employees, had slightly better work ability, and experienced less work-related physical strain at baseline compared to those who died during the follow-up or did not respond to the questionnaire.…”
Section: Evaluation Of the Studymentioning
confidence: 99%
“…The "healthy worker survivor effect" is an ongoing process where those who stay in a specific occupation tend to be healthier than those who exit employment (41). The attrition analysis showed that respondents who were included in the trajectory analysis were slightly younger, more often upper white-collar employees, had slightly better work ability, and experienced less work-related physical strain at baseline compared to those who died during the follow-up or did not respond to the questionnaire.…”
Section: Evaluation Of the Studymentioning
confidence: 99%
“…The healthy worker survivor effect is an ongoing process in which those who stay in a profession tend to be healthier than those who leave employment. 33 Those from blue-collar occupations were more likely than white-collar occupations to drop out or have missing data later on. This could have resulted in an underestimation of the predictive value of work ability within occupational groups.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Thus, is parallels the expanding lifecourse perspective on health inequalities (see, for instance, Carroll et al 1996, Davey Smith et al 1997, Wunsch et al 1996. Self-efficacy is commonly seen as a result of a lifetime development.…”
Section: Developing the Social Stress Model: The Self-efficacy Approachmentioning
confidence: 76%